1993
DOI: 10.1111/j.2044-8325.1993.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Session impact in Stress Management Training

Abstract: The evaluation of stress management training (SMT) programmes suggest that benefits to participants may be due to non-specific factors and not to the technical components of SMT. The current study employed a method of psychotherapy process research to assess the extent to which task, i.e. technique driven, impacts and non-specific impacts are related to outcome. Sixty-two female health service workers participated in six standardized sessions of SMT, each of which contained specific techniques. After training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
2
11
0
3
Order By: Relevance
“…less likely to have any impact on organisational measures such as job satisfaction and productivity (e.g., Cooper & Sadri, 1991;Whatmore, Cartwright, & Cooper, 1999), while organisational and organisational-individual level interventions were more likely to lead to improvements in employee health and organisational performance (e.g., Bond & Bunce, 2001;Cartwright, Cooper, & Whatmore, 2000). The second trend was that individual-level programs were often associated with improvements in mental and emotional wellbeing (e.g., Michie, 1992;Reynolds, Taylor, & Shapiro, 1993) although some authors reported that these benefits were short-lived (e.g., Whatmore, Cartwright, & Cooper, 1999). Finally, other researchers, especially those employing the participatory action research methods (e.g., Bond & Bunce, 2001), felt that the particular level of intervention did not matter.…”
Section: Resultsmentioning
confidence: 99%
“…less likely to have any impact on organisational measures such as job satisfaction and productivity (e.g., Cooper & Sadri, 1991;Whatmore, Cartwright, & Cooper, 1999), while organisational and organisational-individual level interventions were more likely to lead to improvements in employee health and organisational performance (e.g., Bond & Bunce, 2001;Cartwright, Cooper, & Whatmore, 2000). The second trend was that individual-level programs were often associated with improvements in mental and emotional wellbeing (e.g., Michie, 1992;Reynolds, Taylor, & Shapiro, 1993) although some authors reported that these benefits were short-lived (e.g., Whatmore, Cartwright, & Cooper, 1999). Finally, other researchers, especially those employing the participatory action research methods (e.g., Bond & Bunce, 2001), felt that the particular level of intervention did not matter.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, organizational interventions could be locused upon preventing or modifying those situations often regarded as stressful (Reynolds, Taylor, & Shapiro, 1993). This approach would appear to be the most appropriate, particularly as the present study demonstrated consistency in perceptions of the stressfulness of particular events.…”
Section: Discussionmentioning
confidence: 75%
“…Although research suggests these types of interventions can be successful (Berridge, Cooper, and Highley, ; Murphy, ; Reynolds et al, ; Sallis et al, ), the evidence also indicates that this success may be short lived (Ivancevich & Matteson, ). As alluded to earlier, this may be because secondary and tertiary programmes do not attempt to reduce or eliminate the source of the stress itself.…”
Section: Types Of Stress Intervention Researchmentioning
confidence: 99%